The Search for a Cameroonian Model of Democracy or the Search for the Domination of the State Party: 1966-2006 - David Mokam (Cadernos de Estudos Africanos)
1996 and 2006 were two milestones in the political history of Cameroon. They represent, respectively, the establishment of a one-party system in the country and the parliament’s passing of bill that created an independent body to organize country’s elections. The road followed by Cameroon, when compared to those of most African countries, notably Niger and Benin, seems to be different in regards to what political framework was chosen. Analyzing discourse from Cameroonian newspapers in comparison with similar events in Benin and Niger, the article shows that since 1966 the country’s rulers have laboured to create a ‘Cameroonian exception’ to its method of governance, with the eventual aim of having a Cameroonian model of democracy. In reality, the hidden aim has been to perpetuate the domination of the state party in the political landscape of the country.